La notion de dangerosité, maladie infantile de la criminologie - Debuyst, Christian (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1984)
The accent is first of all on the fact (point 1) that the conception of dangerousness is a criminological construct based on the establishment of a causal model within the framework of an objective that is sought. It might be said that this objective is the control of criminal activities and behaviour of groups likely to threaten the social order.It may be said that this point of view (point 2) makes any multidisciplinary approach relatively gratuitous because it does not allow the different disciplines to carry through their own logic.The problem is (point 3) to know how to get rid of this notion without criminology losing its justification and the criminologist/practitioner his usefulness.